Tourist Perceptions of Sapta Pesona in the Poncokusumo Tourism Village - Azzahra Yulia Rochmah; Ambayoen, Mas Ayu; Lintar Brillian Pintakami (CV. Komunitas Dunia Peternakan, 2024)
This research aims to analyze tourists' perceptions of the application of the elements of Sapta Pesona and formulate a strategy for developing Sapta Pesona in the Poncokusumo Tourism Village. Sapta Pesona which includes Safe, Orderly, Clean, Cool, Beautiful, Friendly, and Memorable is a concept designed to increase the attraction of tourists to tourist destinations. The research method used was a survey with a questionnaire distributed to tourists visiting the Poncokusumo Tourism Village. The collected data was analyzed quantitatively to evaluate tourists' perceptions of each element of Sapta Pesona. In addition, a QSPM SWOT analysis was carried out on the results of interviews with tourism village managers and community leaders to identify effective development strategies. The results of the research show that tourists' perceptions of the implementation of Sapta Pesona in the Poncokusumo Tourism Village generally give a positive value with a total score of 331.3, including very good characteristics. Analysis carried out using the QSPM Matrix, the market penetration strategy obtained the highest Total Attractive Score (TAS), namely 5.105. Therefore, this strategy is the best choice for the Poncokusumo Tourism Village.